Potential study of treated effluent organic matter (EFOM) as fertilizer - Nur Shafira, Kamar (2014)
The treated effluent organic matter (EfOM) will be generated as long as human activity continues. World produces large quantities of treated effluent organic matter that much every year and number increasing year after year. Treated EfOM emissions from sewerage treatment plant to channel water may cause pollution. Thus, this approach can be taken to reduce pollution by reuse treated EIOM performance potential sectors which is agriculture. This thesis has revealed the results of a preliminary study in the areas of reuse potential treated EfOM. The study found that sprinkling the plants not only affect plant growth, but also acts as a fertilizer to the plant factor. However, the concentration of bacteria in plants is given anointing the treated EfOM should be given to protecting public health. The treated EfOM also concentration was tested by parameter which are, COD, TSS, NH3-N, Pottasium, and Phosphorus. Characterization treated EfOM from sewerage Treatment Plant at Universiti Malaysia Pahang was matched for reuse. Based on the analysis results, reuse treated EfOM practicable implementation in the landscape Universiti Malaysia Pahang to reduce the cost of chemical fertilizers.